Discourse, Immigration and the Spanish Press: Critical Analysis of the Discourse on the Ceuta and Melilla Border Incident - Teresa Terrón-Caro; Rocío Cárdenas-Rodríguez; Fabiola Ortega-de-Mora (Societies, 2022)
The Spanish press relayed the events that unfolded during the migratory incident that occurred in Ceuta and Melilla on 17 May 2021. Considering the media’s key role in social and ideological construction, the purpose of this article is to analyze the informative treatment that the Spanish press gave to this incident, contributing to the study of the image that is shown about the migrant population in the media. For this, the present qualitative study performed a critical analysis, using the Atlas software. Ti 8, of the discourse featuring in the newspaper publications of El País, El Mundo, La Vanguardia and ABC. The results demonstrated the following tendencies: a negative-tone discourse; the invisibility of migrant women; and a “we” vs. “them” narrative. In the light of this reality, we suggest that improvements be made, including a shift in the media’s populist discourse and a greater focus on diasporas.